PENGARUH PANDANGAN HIDUP MASYARAKAT JAWA TERHADAP MODEL KEPEMIMPINAN (Tinjauan Filsafat Sosial) - Siswanto, Dwi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2010)
Relevance between world view of Javanese and adopted model of leadership is reflected in their moral rules that emphasizes attitudes, such as patient (narima), introspection (waspada-eling),humble (andap asor and prasaja) which is applied by each individual in realizing harmony of their society. Java’s leadershipmodel is paternalism and charismatic. They are respectful andobedient to their leader because of his/her charisma rather than acompulsion.Keywords: Javanism/ Javanese way of life, leadership, narima,waspada-eling, andap asor, prasaja, paternalism.